Hepatic Actinomycosis with Infiltration of the Diaphragm and Right Lung: A Case Report - Tasbirul Islam; Muhammad Nauman Athar; Muhammad Kamran Athar; Mohammed Haris Umer Usman; Baqir Misbah (Canadian Respiratory Journal)
Actinomycosis is an indolent, slowly progressive infection caused by anaerobic or microaerophilic bacteria of the genus Actinomyces. Actinomycosis has a myriad of clinical presentations, inducing both a suppurative and granulomatous inflammatory response. The infection spreads contiguously through anatomical barriers and frequently forms external sinuses. The most common clinical presentations are cervicofacial, thoracic, abdominal and, in females, genital. Classic features include purulent foci surrounded by dense fibrosis that, over time, cross natural boundaries into contiguous structures, with the formation of fistulas and sinus tracts in some cases. Hepatic actinomycosis presents as single or multiple abscesses or masses. Reported here is the unusual occurrence of actinomycosis of the liver involving the diaphragm and right lung. The present case illustrates the difficulties in diagnosing this rare and unrecognized disease.